PENINGKATAN KETERAMPILAN BERPIKIR KRTIS DAN RASA INGIN TAHU PADA PEMBELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING - Wiwin Fira Nurul Badi'ah; Hasan Subekti; Wahyu Budi Sabtiawan (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to describe the improvement of critical thinking skills and curiosities of Junior High School students’ in science learning using problem-based learning. This research design used one group pretest-postest. This research involved 33 students of class VIII-A of MTs Miftahul Ulum Magerari in Academic Year 2021/2022. This research’s data collection methods included observation , test, and questionnaires. The data analysis technique used in this research was quatitative statistics by using Wilcoxon signed rank test. The results showed that implementation of problem-based learning can improve critical thinking skills and student curiosities in science learning.